Method for synergistic activation of cobalt hydroxycarbonate electrode by doping with molybdenum sulfide and phosphorus

Through the collaborative auxiliary activation technology of molybdenum sulfide modification and phosphorus doping, the problems of low capacity and poor cycle stability of CCHH electrode materials are solved, significantly improving capacity and charging voltage, improving electrochemical performance, and achieving higher energy density and cycle stability.

CN115863067BActive Publication Date: 2025-01-14XIAN XD POWER CAPACITOR CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310045893.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-30
Publication Date
2025-01-14
Estimated Expiration
2043-01-30

AI Technical Summary

Technical Problem

The actual capacity of hydroxycobalt carbonate (CCHH) electrode material is low and the cycle stability is not ideal. It is mainly due to the limitations of conductivity and microstructure, which causes the cobalt-based material to change violently during the charge and discharge process, and the active material departs from the current collector and the capacity is attenuated.

Method used

Molybdenum sulfide modification and phosphorus doping collaborative auxiliary activation methods were adopted to prepare CCHH precursors by hydrothermal method, Mo-S modification and P-doping were performed, and then annealed in a CVD tube furnace and electrochemical activation was performed to form CCHH/ Mo-S/P electrodes inhibit phase transition and enhance conductivity and surfactivity sites.

Benefits of technology

The capacity and cycle stability of the CCHH electrode have been significantly improved, with the capacity increased from 1.29F/cm2 to 4.4F/cm2, the charging voltage increased from 0.5V to 0.55V and above, the internal resistance and charge transfer resistance decreased, maintaining 85% and above The capacity is repeated charge and discharge stability under high current density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115863067B_ABST
    Figure CN115863067B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for synergistically activating a cobalt carbonate hydroxyl electrode by doping molybdenum sulfide and phosphorus. First, a cobalt carbonate hydroxyl precursor is prepared on a nickel foam substrate; then, molybdenum sulfide is loaded on the surface of CCHH by a hydrothermal method to obtain CCHH / Mo‑S; then, CCHH / Mo‑S is phosphated to obtain CCHH / Mo‑S / P; finally, CCHH / Mo‑S / P is activated by a chronopotentiometry to obtain the final product CCHH / Mo‑S / P / A. CCHH / Mo‑S / P / A has a high activation temperature of 40 mA / cm 2 Under high current, after repeated charge and discharge for 10,000 times, the capacity retention rate is still as high as 85% or more, indicating that the activation strategy assisted by molybdenum sulfide and phosphorus doping not only significantly improves the capacity of CCHH, but also the obtained sample has excellent cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of supercapacitors, and specifically relates to a method for improving the electrochemical performance of cobalt hydroxy carbonate by synergistic auxiliary activation of molybdenum sulfide modification and phosphorus doping. Background Art

[0002] Supercapacitors are energy storage devices with great application prospects due to their high power density and long cycle life. However, compared with lithium-ion batteries, the energy density of supercapacitors still needs to be improved. Among them, increasing the capacity of electrode materials is one of the important ways to improve the energy density of supercapacitors.

[0003] Among different electrode materials, cobalt carbonate hydroxy (CCHH) has attracted widespread attention because of its high theoretical capacity. However, limited by conductivity and microstructure, the actual capacity of CCHH is generally much lower than its theoretical capacity, and the cobalt-based material undergoes drastic phase changes during repeated charge and discharge, which can easily cause the active material to detach from the current collector, resulting in further capacity decay during the cycle. Studies have shown that P doping can effectively improve the conductivity of the material, thereby increasing its capacity. However, the actual capacity of the material is not only related to conductivity, but also to the micromorphology of the active material and the active sites on its surface in contact with the electrolyte. Therefore, the effect of P doping alone on improving capacity is limited. In addition, P doping cannot alleviate the drastic phase changes of cobalt-based materials during repeated charge and discharge, and its improvement on cycle stability is also very limited. Summary of the invention

[0004] The purpose of the present invention is to address the problems of low actual specific capacity and unsatisfactory cycle stability of CCHH electrode materials, and to propose a method for improving the electrochemical performance of cobalt hydroxycarbonate by synergistic auxiliary activation of molybdenum sulfide modification and phosphorus doping.

[0005] The technical scheme of the present invention comprises the following steps: using nickel foam as a substrate and adopting a hydrothermal method to obtain a CCHH precursor; using the hydrothermal method again to perform Mo-S modification on CCHH to obtain CCHH / Mo-S; using sodium hypophosphite as a phosphorus source, annealing the CCHH / Mo-S in a CVD tube furnace to obtain CCHH / Mo-S / P; and finally performing an activation treatment on the CCHH / Mo-S / P to obtain a final product CCHH / Mo-S / P.

[0006] The technical method of the present invention comprises the following steps:

[0007] (1) preparing a CCHH precursor: adding a mixed aqueous solution of cobalt nitrate and urea to nickel foam, and then sealing and performing a hydrothermal reaction to obtain a CCHH precursor;

[0008] (2) Preparation of CCHH / Mo-S: Add ammonium fluoride to an aqueous solution of ammonium molybdate tetrahydrate and thioacetamide, add the CCHH precursor prepared in step (1), seal and perform a hydrothermal reaction to obtain CCHH / Mo-S;

[0009] (3) placing sodium hypophosphite and the CCHH / Mo-S prepared in step (2) in a non-contact manner in a CVD tube furnace, filling with argon, and heating and calcining to obtain CCHH / Mo-S / P;

[0010] (4) Preparation of CCHH / Mo-S / P / A: Using the CCHH / Mo-S / P prepared in step (3) as a working electrode, a platinum sheet as a counter electrode, a mercury / mercury oxide electrode as a reference electrode, and a potassium hydroxide solution as an electrolyte, the CCHH / Mo-S / P is subjected to constant current charging treatment in a positive potential window by using a chronopotentiometry in an electrochemical workstation three-electrode system to obtain an activated CCHH / Mo-S / P / A electrode.

[0011] In step (1), the hydrothermal reaction temperature is 100-120° C., and the reaction time is 5-8 hours. In the preferred embodiment, the hydrothermal reaction temperature is 100° C., and the reaction time is 6 hours.

[0012] In step (2), the hydrothermal reaction temperature is 180-200°C, and the reaction time is 12-18 hours. In the preferred embodiment, the hydrothermal reaction temperature is 180°C, and the reaction time is 15 hours.

[0013] In step (3), the calcination temperature is 300-350°C and the calcination time is 2-3 hours. In the preferred embodiment, the calcination temperature is 300°C and the calcination time is 2 hours.

[0014] The molar ratio of the cobalt nitrate, urea, ammonium molybdate, thioacetamide, ammonium fluoride and sodium metaphosphate is 1:5-10:0.01-0.06:0.2-1.0:0.1-0.3:0.1-0.4.

[0015] As a preferred embodiment, the molar ratio of cobalt nitrate, urea, ammonium molybdate, thioacetamide, ammonium fluoride and sodium metaphosphate is 1:7.5:0.04:0.665:0.125:0.228.

[0016] In step (4), the KOH concentration is 1-3M, the low potential is 0-0.2V, the high potential window is 0.8-1.5V, the current size is 0.01-0.05A, and the charging time is 3-5h.

[0017] In step (4), the KOH concentration is 1 M, the low potential is 0 V, the high potential window is 0.8 V, the current is 0.01 A, and the charging time is 3 h.

[0018] In the technical solution of the present invention, CCHH is first prepared and then modified with Mo-S. Mo-S can inhibit the drastic phase change of CCHH to a certain extent and improve the cyclic stability of CCHH. Then P doping is performed to improve the conductivity. On this basis, the sample is activated to induce the growth of uniform nanosheets inside the material, significantly increasing the surface active sites of the sample. The study found that after Mo-S modification, the sample was covered with small nanosheets, and a large number of cracks appeared on the entire sample surface, which can effectively inhibit the drastic phase change of CCHH during the cycle and relieve the stress caused by the phase change. After further P doping and activation treatment, uniform micron sheets with a thickness of about 20nm grew on the sample surface, repairing the large number of cracks that appeared after Mo-S modification, and forming a three-dimensional network inside the material, providing a fast channel for the transfer of charges. In addition, the newly grown micron sheets increased the specific surface area of ​​the sample from 78.78 to 90m 2 g -1 The above means that the surface active sites are increased, so the capacity is further improved. Through charge and discharge tests, we also found that after activation treatment, the voltage that the sample can reach when charged is increased from 0.5V to 0.55V and above. Due to the energy density Therefore, the increase in voltage is conducive to improving the energy density of the sample when assembling the device. Electrochemical impedance spectroscopy analysis shows that the internal resistance and charge transfer resistance of the sample are reduced through this molybdenum sulfide modification and phosphorus doping synergistic auxiliary activation strategy. Therefore, the present invention adopts molybdenum sulfide modification and phosphorus doping synergistic auxiliary activation strategy to make CCHH at 25mA / cm 2 At a current density of 1.29 F / cm 2 Increased to 4.4F / cm 2 Above, and has excellent cycle stability at 40mA / cm 2 After repeated charge and discharge for 10,000 times at a high current density, the capacity retention rate is still as high as 85% or more.

[0019] The technical solution of the present invention applies the electrode obtained above to a supercapacitor.

[0020] In the present invention, after the treatment in step (2), the sample is covered with small nanosheets, and a large number of cracks appear on the entire sample surface, which can effectively inhibit the drastic phase change of CCHH during the cycle and relieve the stress generated by the phase change, thereby preventing the active material from falling off the substrate surface and relieving the capacity decay of the material during the cycle. After the treatment in steps (3) and (4), uniform micron sheets with a thickness of about 20 nm grow on the sample surface, repairing a large number of cracks that appear after Mo-S modification, and forming a three-dimensional network inside the material, providing a fast channel for charge transmission. The newly grown micron sheets increase the specific surface area of ​​the sample from 78.78 to 90 m 2 g-1 The above increases the surface active sites. Through charge and discharge tests, we also found that after activation treatment, the voltage that the sample can reach when charged is increased from 0.5V to 0.55V and above, which is conducive to the sample to obtain a greater energy density. In addition, through the coordinated auxiliary activation strategy of molybdenum sulfide modification and phosphorus doping, the internal resistance and charge transfer resistance of the sample are reduced. Therefore, the coordinated auxiliary activation strategy of molybdenum sulfide modification and phosphorus doping not only increases the surface active sites of the sample and improves the conductivity, but also inhibits the drastic phase change during the cycle and relieves the corresponding stress, ultimately significantly improving the capacity and cycle stability of CCHH. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 , (a, b) are SEM images of CCHH / Mo-S in Example 5, (c, d) are SEM images of CCHH / Mo-S P / A in Example 1, and (e, f) are TEM images of CCHH / Mo-S P / A in Example 1.

[0022] Figure 2 1 is the charge and discharge curve of the CCHH / Mo-SP / A sample at different current densities in Example 1.

[0023] Figure 3 2 is the charge and discharge curve of the CCHH / P / A sample at different current densities in Example 2.

[0024] Figure 4 : The charge and discharge curves of the CCHH / Mo-S / A sample in Example 3 at different current densities.

[0025] Figure 5 : The charge and discharge curves of the CCHH / Mo-S / P sample in Example 4 at different current densities.

[0026] Figure 6 : The charge and discharge curves of the CCHH / Mo-S sample in Example 5 at different current densities.

[0027] Figure 7 : The charge and discharge curves of the CCHH sample in Example 6 at different current densities.

[0028] Figure 8 It is the EIS and high frequency region enlarged view of each sample in Examples 1-6. DETAILED DESCRIPTION

[0029] In order to further understand the content and features of the present invention, embodiments of the present invention are given below. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0030] The experimental methods in the following examples are conventional methods unless otherwise specified.

[0031] Example 1

[0032] (1) Preparation of CCHH precursor: 4 mmol cobalt nitrate and 30 mmol urea were added to deionized water, stirred until fully dissolved, and then the prepared solution was poured into the inner tank of the reactor. Clean nickel foam was placed in the inner tank, sealed with a stainless steel jacket, heated at 100°C for 6 h, taken out, ultrasonically cleaned in deionized water and anhydrous ethanol, and dried in an oven to obtain a CCHH precursor.

[0033] (2) Preparation of CCHH / Mo-S: 0.16 mmol of ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) and 2.66mmol thioacetamide (TAA) are dissolved in 40mL deionized water to obtain a transparent solution. Then 0.5mmol ammonium fluoride (NH4F) is added and further stirred until completely dissolved. The prepared mixed solution and a piece of CCHH precursor are placed in a stainless steel reactor, sealed and placed in a 180℃ oven for 15 hours. After the reaction is completed, the nickel foam is taken out, washed with direct washing water, and dried at 60℃.

[0034] (3) Preparation of CCHH / Mo-S / P: 0.91mmol sodium hypophosphite (NaH2PO2) and a piece of CCHH / Mo-S were placed in two porcelain boats of a CVD tube furnace. The tube furnace was closed and 50sccm of high-purity Ar was injected for 15 minutes. The furnace was then heated from room temperature to 300°C at a heating rate of 5°C / min, and then naturally cooled to room temperature after being kept at 300°C for 2 hours. The Ar atmosphere was maintained throughout the process, and the resulting sample was recorded as CCHH / Mo-S / P.

[0035] (4) Preparation of CCHH / Mo-S / P / A: Using CCHH / Mo-S / P as the working electrode, platinum as the counter electrode, mercury / mercury oxide electrode as the reference electrode, and 1 M KOH as the electrolyte, the chronopotentiometry in the three-electrode system of the electrochemical workstation was used. The low potential window was set to 0 V, the high potential window was set to 0.8 V, the current size was 0.01 A, and the charging time was 3 h. The CCHH / Mo-S / P / A electrode after charging treatment was obtained.

[0036] Among them, steps (2), (3) and (4) are key steps. Step (2) makes the sample covered with Mo-S nanosheets (see Appendix Figure 1a and 1b), and a large number of cracks appear on the entire sample surface, which can effectively inhibit the drastic phase change of CCHH during the cycle and relieve the stress generated by the phase change, thereby preventing the active material from falling off the substrate surface and alleviating the capacity decay of the material during the cycle; steps (3) and (4) cause the sample surface to grow uniform micron sheets with a thickness of about 20 nm, repairing the large number of cracks that appear after Mo-S modification, and forming a three-dimensional network inside the material, providing a fast channel for charge transfer; the newly grown micron sheets increase the specific surface area of ​​the sample from 78.78 to 90 m 2 g -1 The above increases the surface active sites. Through charge and discharge tests, we also found that after activation treatment, the voltage that the sample can reach when charged is increased from 0.5V to 0.55V and above, which is conducive to the sample obtaining a greater energy density. In addition, through the step (3) molybdenum sulfide modification and step (4) phosphorus doping synergistic auxiliary activation strategy, the internal resistance and charge transfer resistance of the sample are reduced. Therefore, after the above steps (3), (4), and (5), the electrochemical performance of CCHH is finally significantly improved.

[0037] Attached Figure 1 (a, b) are SEM images of CCHH / Mo-S. It can be seen that the sample surface is covered with small nanosheets, and a large number of cracks appear on the entire sample surface. (c, d) are SEM images of CCHH / Mo-S / P / A electrodes at different magnifications. (e, f) are TEM images of the response. It can be seen that after activation treatment, uniform microsheets with a thickness of about 20 nm grow on the sample surface, repairing a large number of cracks that appeared after Mo-S modification, and forming a three-dimensional network inside the material, which can provide a fast channel for charge transfer and provide more active sites for electrochemical reactions, which can greatly improve the specific capacitance value. Figure 2 The charge and discharge curves of CCHH / Mo-S / P / A samples at different current densities.

[0038] Example 2

[0039] Compared with Example 1, Example 2 did not perform the Mo-S modification in step (2), and the rest was the same as Example 1. Figure 3 The charge and discharge curves of the CCHH / P / A sample obtained in Example 2 at different current densities.

[0040] Example 3

[0041] Compared with Example 1, Example 3 does not perform phosphorus doping in step (3), and the rest is the same as Example 1. Figure 4 The charge and discharge curves of the CCHH / Mo-S / A sample obtained in Example 3 at different current densities.

[0042] Example 4

[0043] Compared with Example 1, Example 4 did not perform the activation treatment in step (4), and the rest was the same as Example 1. Figure 5 The charge and discharge curves of the CCHH / Mo-S / P sample obtained in Example 4 at different current densities.

[0044] Example 5

[0045] Compared with Example 1, Example 5 does not carry out the phosphating treatment in step (3) and the activation treatment in step (4), and the rest is the same as Example 1. Figure 6 The charge and discharge curves of the CCHH / Mo-S sample obtained in Example 5 at different current densities.

[0046] Example 6

[0047] Compared with Example 1, Example 6 does not perform the Mo-S modification in step (2), the phosphorus doping in step (3) and the activation treatment in step (4), and the rest is the same as Example 1. Figure 7 The charge and discharge curves of the CCHH sample obtained in Example 6 at different current densities.

[0048] To further illustrate the effect of molybdenum sulfide modification and phosphorus doping assisted activation strategy on the electrochemical performance of CCHH, we compared the capacity of each sample in Examples 1-6. According to the charge-discharge curve and capacity calculation formula The corresponding capacity values ​​are calculated and the results are shown in Table 1. It can be seen from the table that when the current density is 25mA / cm 2 When the capacity of CCHH / Mo-S / P / A reaches 4.41F / cm 2 , which are 8.3, 2.5, 1.5, 6.3, and 3.4 times of CCHH / P / A, CCHH / Mo-S / A, CCHH / Mo-S / P, CCHH / Mo-S, and CCHH, respectively. This shows that only after the coordinated activation of molybdenum sulfide modification and phosphorus doping can the maximum capacity be obtained. In addition, by comparing the charge and discharge curves of different samples, we also found that the activation treatment can increase the sample charging voltage from 0.5V to 0.55V. Due to the energy density The increase in voltage is beneficial to improving the energy density when assembling samples into devices.

[0049] Attached Figure 8 a is the EIS curve, Figure 8Middle b is the corresponding high-frequency magnified image. By comparing the first intersection of the semicircular area of ​​the curve and the Z' axis (the results are shown in Appendix 2), the internal resistances of CCHH / Mo-S / P / A, CCHH / P / A, CCHH / Mo-S / A, CCHH / Mo-S / P, CCHH / Mo-S, and CCHH electrodes are 0.96Ω, 1.24Ω, 1.16Ω, 1.1Ω, 1.4Ω, and 1.6Ω, respectively, proving that the synergistic auxiliary activation energy of molybdenum sulfide modification and phosphorus doping can effectively reduce the internal resistance.

[0050] Appendix 1 shows the parameter values ​​for calculating the specific capacitance of the samples in Examples 1-5.

[0051] CCHH / P / A refers to samples without Mo-S modification.

[0052] CCHH / Mo-S / A refers to: samples that have not been phosphated.

[0053] CCHH / Mo-S / P refers to the sample without activation treatment.

[0054] CCHH / Mo-S refers to samples that have not been phosphated or activated.

[0055] CCHH refers to: samples without Mo-S modification, phosphating and phosphating treatment

[0056]

[0057] Appendix 2 shows the internal resistance (Rs) of each sample in Examples 1-5.

[0058] sample Rs CCHH / Mo-S / P / A 0.96 CCHH / P / A 1.24 CCHH / Mo-S / A 1.16 CCHH / Mo-S / P 1.1 CCHH / Mo-S 1.4 CCH 1.6 .

Claims

1. A method for synergistically activating a cobalt hydroxycarbonate electrode by doping molybdenum sulfide and phosphorus, characterized in that: The following steps are involved: (1) Preparation of CCHH precursor: adding a mixed aqueous solution of cobalt nitrate and urea to nickel foam, and then sealing and performing a hydrothermal reaction to obtain a CCHH precursor; (2) Preparation of CCHH / Mo-S: Add ammonium fluoride to an aqueous solution of ammonium molybdate tetrahydrate and thioacetamide, add the CCHH precursor prepared in step (1), seal and perform a hydrothermal reaction to obtain CCHH / Mo-S; (3) placing sodium hypophosphite and the CCHH / Mo-S prepared in step (2) in a non-contact manner in a CVD tube furnace, filling with argon, and heating and calcining to obtain CCHH / Mo-S / P; (4) Preparation of CCHH / Mo-S / P / A: Using the CCHH / Mo-S / P prepared in step (3) as the working electrode, a platinum sheet as the counter electrode, a mercury / mercury oxide electrode as the reference electrode, and a potassium hydroxide solution as the electrolyte, the CCHH / Mo-S / P is subjected to constant current charging treatment in the positive potential window by using the chronopotentiometry in the three-electrode system of the electrochemical workstation to obtain an activated CCHH / Mo-S / P / A electrode.

2. The method for synergistically activating cobalt hydroxycarbonate electrode by doping molybdenum sulfide and phosphorus according to claim 1, characterized in that: In step (1), the hydrothermal reaction temperature is 100-120° C. and the reaction time is 5-8 h.

3. The method for synergistically activating cobalt hydroxycarbonate electrode by doping molybdenum sulfide and phosphorus according to claim 1, characterized in that: In step (2), the hydrothermal reaction temperature is 180-200° C. and the reaction time is 12-18 h.

4. The method for synergistically activating cobalt hydroxycarbonate electrode by doping molybdenum sulfide and phosphorus according to claim 1, characterized in that: In step (3), the calcination temperature is 300-350°C and the calcination time is 2-3h.

5. The method for synergistically activating cobalt hydroxycarbonate electrode by doping molybdenum sulfide and phosphorus according to claim 1, characterized in that: The molar ratio of cobalt nitrate, urea, ammonium molybdate, thioacetamide, ammonium fluoride and sodium metaphosphate is 1:5-10:0.01-0.06:0.2-1.0:0.1-0.3:0.1-0.

4.

6. The method for synergistically activating cobalt hydroxycarbonate electrode by doping molybdenum sulfide and phosphorus according to claim 5, characterized in that: The molar ratio of cobalt nitrate, urea, ammonium molybdate, thioacetamide, ammonium fluoride and sodium metaphosphate is 1:7.5:0.04:0.665:0.125:0.

228.

7. The method for synergistically activating cobalt hydroxycarbonate electrode by doping molybdenum sulfide and phosphorus according to claim 1, characterized in that: In step (4), the KOH concentration is 1-3M, the low potential is 0-0.2V, the high potential window is 0.8-1.5V, the current is 0.01-0.05A, and the charging time is 3-5h.

8. The method for synergistically activating cobalt hydroxycarbonate electrode by doping molybdenum sulfide and phosphorus according to claim 7, characterized in that: In step (4), the KOH concentration is 1 M, the low potential is 0 V, the high potential window is 0.8 V, the current is 0.01 A, and the charging time is 3 h.

Citation Information

Patent Citations

  • Lithium ion battery negative electrode material and preparation method

    CN107681133A

  • Method for improving capacity of cobalt-based hydroxide containing embedded anions

    CN115440510A